SEMA3C Promotes Cervical Cancer Growth and Is Associated With Poor Prognosis - Liu, Ruoyan; Shuai, Yanjie; Luo, Jingtao; Zhang, Ze (Frontiers in Oncology, 2019)
Introduction: Aberrant activation of Semaphorin3C(SEMA3C) is widespread in human cancers. We aimed to analyze SEMA3C expression in cervical cancer and investigate the role of SEMA3C in cervical cancer and its underlying mechanism, which is important for exploring new therapeutic targets and prognostic factors. Materials and Methods: The expression of SEMA3C was examined in paraffin-embedded cervical cancer specimens. In vivo and in vitro assays were performed to validate the effect of SEMA3C on cervical cancer cell proliferation and p-ERK pathway activation. Gene Set Enrichment Analysis (GSEA) was performed using The Cancer Genome Atlas (TCGA) data set. Results: SEMA3C expression was associated with poor survival in both the TCGA cohort and our cohort. Silencing of SEMA3C suppressed cervical cancer cell proliferation, colony formation ability, and the activation of the p-ERK signaling pathway in vitro. SEMA3C depletion inhibited tumor growth in vitro. GSEA also showed that the epithelial mesenchymal transition (EMT), TGFβ signaling pathway, angiogenesis, and extracellular matrix (ECM) receptor interactions are associated with a high SEMA3C expression phenotype. Conclusion: SEMA3C is correlated with poor prognosis of cervical cancer patients and promotes tumor growth via the activation of the p-ERK pathway.